An Island Mass Effect Resolved Near Mo’orea, French Polynesia - James, Anna K.; Washburn, Libe; Gotschalk, Chris; Maritorena, Stéphane; Alldredge, Alice; Nelson, Craig E.; Hench, James L.; Leichter, James J.; Wyatt, Alex S. J.; Carlson, Craig A. (Frontiers in Marine Science, 2020)
We sought to resolve the extent, variability, and magnitude of productivity enrichment around a high tropical island consistent with the phenomenon of an Island Mass Effect (IME). Key biogeochemical constituents and physical oceanographic parameters were measured offshore over the upper 500 m from July 27 to August 7, 2014 around the Society Island of Mo’orea in French Polynesia in association with the nearshore measurements of the Mo’orea Coral Reef Long Term Ecological Research program. High-resolution synoptic sampling in a rectangular grid around the island revealed vertical and horizontal patterns in hydrographic conditions, inorganic nutrients, rates of productivity, and concentrations of organic matter that are characteristic of oligotrophic gyre ecosystems. Within the upper euphotic zone (0 – 75 m), levels of net primary productivity (NPP), chlorophyll a (Chl), heterotrophic bacterioplankton productivity (BP), and particulate organic carbon (POC) exhibited concurrent enhancement at stations located within 5 to 15 km of shore, relative to stations farther offshore. These observations of enhanced productivity near an island are consistent with an IME. Particulate organic matter nitrogen isotopes (POM- δ15N) were significantly lower near the island than at stations farther offshore, further emphasizing spatial differences in water column biogeochemistry consistent with an IME. Vertical profiles suggest thermocline shoaling and mixing associated with the pycnocline impinging on the island’s submerged flanks and coral reef slope may have contributed to the decreasing depth and increasing intensity of chlorophyll-a concentration in the DCM at nearshore stations relative to farther offshore. Shipboard measurements of an anticyclonic flow within the upper 75 m of the water column in the vicinity of Mo’orea suggest that retention of inorganic nutrients and organic matter near Mo’orea may also have contributed to the patterns in NPP, Chl, BP, POC and POM- δ15N, providing a potential mechanistic understanding of the processes driving an IME.